Endoscopic Resection of Skull Base Teratoma in Klippel-Feil Syndrome through Use of Combined Ultrasonic and Bipolar Diathermy Platforms. (4th January 2017) - Edward, Justin A.; Psaltis, Alkis J.; Williams, Ryan A.; Charville, Gregory W.; Dodd, Robert L.; Nayak, Jayakar V.
Abstract : Klippel-Feil syndrome (KFS) is associated with numerous craniofacial abnormalities but rarely with skull base tumor formation. We report an unusual and dramatic case of a symptomatic, mature skull base teratoma in an adult patient with KFS, with extension through the basisphenoid to obstruct the nasopharynx. This benign lesion was associated with midline palatal and cerebral defects, most notably pituitary and vertebrobasilar arteriolar duplications. A multidisciplinary workup and a complete endoscopic, transnasal surgical approach between otolaryngology and neurosurgery were undertaken. Out of concern for vascular control of the fibrofatty dense tumor stalk at the skull base and need for complete teratoma resection, we successfully employed a tissue resection tool with combined ultrasonic and bipolar diathermy to the tumor pedicle at the sphenoid/clivus junction. No CSF leak or major hemorrhage was noted using this endonasal approach, and no concerning postoperative sequelae were encountered. The patient continues to do well now 3 years after tumor extirpation, with resolution of all preoperative symptoms and absence of teratoma recurrence. KFS, teratoma biology, endocrine gland duplication, and the complex considerations required for successfully addressing this type of advanced skull base pathology are all reviewed herein.